2008
DOI: 10.1136/emj.2008.058206
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of signs, treatment and need for urgent management in patients presenting with an acute ischaemic stroke or transient ischaemic attack: a prospective study

Abstract: Community knowledge of ischaemic stroke needs to be enhanced so that individuals present earlier, leading to timely management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 18 publications
0
15
1
Order By: Relevance
“…However, awareness of the importance of early intervention and early rehabilitation remained insufficient. In addition, Stead et al and Kim et al both reported that learning of the existence of thrombolytic therapy is associated with early diagnosis by a doctor (10,17). In the present study, however, knowledge did not extend as far as the sort of stroke treatments that are currently available, and there was no specific knowledge of endovascular therapy using the Merci Retrieval System or brain protective agents, which are the latest therapies.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…However, awareness of the importance of early intervention and early rehabilitation remained insufficient. In addition, Stead et al and Kim et al both reported that learning of the existence of thrombolytic therapy is associated with early diagnosis by a doctor (10,17). In the present study, however, knowledge did not extend as far as the sort of stroke treatments that are currently available, and there was no specific knowledge of endovascular therapy using the Merci Retrieval System or brain protective agents, which are the latest therapies.…”
Section: Discussioncontrasting
confidence: 60%
“…The first factor is Detection, meaning that the speed with which ordinary citizens can recognize symptoms is important. Numerous reports have also stressed the importance of rapidly identifying a stroke and calling for an ambulance or emergency personnel to decrease prehospital delay (2,(7)(8)(9)(10)17). Educational activities related to strokes are thus likely to be highly effective in stressing the importance of providing preventative measures and a rapid response at stroke onset.…”
Section: Discussionmentioning
confidence: 99%
“…This behaviour is recognised by the American Heart Association Council as ‘the major factor limiting delivery of definitive treatment’. In a US study, only 52% of patients presenting to an emergency department (ED) with a TIA or stroke thought immediate presentation was crucial 2. Similarly, in a recent survey of a UK population, a high proportion of patients suffering a TIA would wait for a recurrence before seeking medical advice: 41–95% depending on the symptom 3.…”
mentioning
confidence: 99%
“…In a retrospective populationbased US study, 2.3% of responders had been given a diagnosis of TIA but a further 3.2% reported TIA symptoms for which they did not seek medical care. 27 Furthermore, studies of actual rather than hypothetical intended behaviour in TIA are often of cases ascertained only in secondary or tertiary care settings, [28][29][30] which may also limit the generalisability of such findings.…”
Section: Strengths and Limitationsmentioning
confidence: 99%